Effect of Main Bearing Surface Profile on Crankshaft Lubrication and Vibration Characteristic - Guixiang Zhu; Junsheng Zhao; Chunjian Li; Jialin Wang; Min Liu; Zhihao Yang (Jixie chuandong)
Taking the main bearing-main journal of a six-cylinder diesel engine as the research object，based on the elastic- -fluid lubrication theory and the micro-bump contact theory and considering factors such as journal misalignment and main bearing surface roughness，the main bearing lubrication characteristics model under the flexible whole body is established，and the influence of the main bearing surface profile on the main bearing lubrication characteristics and main journal vibration characteristics is analyzed. The results show that，compared with the result that does not take into account the main bearing surface profile，when the main bearing surface profile is included，the minimum oil film thickness of the main bearing is increased by 75.53%，the maximum oil film pressure is reduced by 6.15%，the average friction loss is reduced by 2%，the horizontal flexural vibration amplitudes of the main journal is reduced by 6%，the vertical flexural vibration amplitudes is reduced by 5%，and both the axial vibration and torsional vibration amplitudes are reduced by 2%. With the increase of the main bearing surface profile height，the minimum oil film thickness of the main bearing increases，the maximum oil film pressure decreases，the average friction loss decreases，and both the maximum roughness contact force amplitude and the number of occurrences are reduced; the amplitudes of flexural vibration，axial vibration and torsional vibration of the main journal are all reduced.